Seepage strength of the dam soil in the area of a round-shaped culvert spillway - G. V. Orekhov; Tran Manh Cuong (Vestnik MGSU)
Introduction. There are many destructions of earth dams in the world due to the loss of seepage strength of soils of the dam body or foundation. The seepage stability of soils is directly related to the phenomenon of hydraulic fracturing (HF), so prevention of conditions causing hydraulic fracturing is a very important task in the design and operation of earth dams. Hydraulic fracturing is closely related to uneven settlement of the dam soils and building structures. In earth dams, the phenomenon of uneven settlement often occurs in the areas between the dam soil and the side masses of the dam site, the dam soil and concrete structures, such as culverts and spillways, foundation structural elements, the impervious core of the dam and adjacent soil zones. The article is devoted to the study of the seepage stability of soil dams in the area of round-shaped culvert spillway.Materials and methods. The study was carried out with the help of numerical modelling using Plaxis software package. The Bung Bung earth dam (Vietnam) was taken as an object of study.Results. The results of the studies showed that the normal stress around the culvert was reduced to a level much lower than the water pressure in the seepage flow with a high probability of hydraulic fracturing in the volume of soil below the spillway. Thus, hydraulic fracturing can occur in these areas. The article proposes two structural approaches to prevent hydraulic fracturing: to change the cross-sectional shape of the culvert and to install a clay jacket around the spillway. Both approaches were tested numerically. The calculations demostrated that the application of both methods reduces the conditions for the occurrence of hydraulic fracturing near the culvert.Conclusions. Dam failure due to hydraulic fracturing can cause serious damage. The implementation of methods to prevent hydraulic fracturing is important to ensure the safe dam conditions.